Continuous Fetal Monitoring During Electroconvulsive Therapy: A Prospective Observation Study - Rabie, Nader; Shah, Ronak; Ray-Griffith, Shona; Coker, Jessica L; Magann, Everett F; Stowe, Zachary N (International journal of women's health, 2021)
The use of electroconvulsive therapy in pregnancy has been limited by concerns about its effects on fetal well-being, despite limited evidence that suggests it is safe and effective. No studies have utilized continuous fetal heart rate monitoring during electroconvulsive therapy sessions. We aimed to describe the fetal heart rate patterns of patients undergoing electroconvulsive therapy. This study is a prospective case series of pregnant patients undergoing electroconvulsive therapy with continuous fetal heart rate monitoring. University-based hospital. Pregnant patients with a psychiatric indication for electroconvulsive therapy. Patients underwent fetal heart rate monitoring immediately prior, during and immediately after ECT therapy. Characterization of the fetal heart rate tracing. Five subjects underwent 44 electroconvulsive therapy sessions. Continuous fetal monitoring was performed on 34 of the sessions. Transient fetal heart rate decelerations occurred in 4 sessions, all self-resolved and none required intervention. This case series is the first to report the results of continuous FHR monitoring during electroconvulsive therapy. The most common finding was a transient, self-resolving bradycardia that was not associated with adverse perinatal outcomes. This supports the opinion that electroconvulsive therapy is a safe treatment option in pregnancy in women with severe mental disease.